DAMPAK PENILAIAN PRESTASI KERJA E-SKP TERHADAP KEPUASAN KERJA PADA KOMITMEN ORGANISASI - R. JOKO KUSMARHENOTO; MURYATI MURYATI; NASHARUDDIN MAS (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2021)
ABSTRACT This research aims to obtain empirical evidence of the ability of the E-SKP Job Performance Assessment in increasing Organizational Commitment both directly and through intervening Job Satisfaction. This type of research was quantitative research, and the method used was SEM-PLS. The data were obtained through a questionnaire distributed to 53 instructors UPTPK Singosari, Wonojati, and Pasuruan.Empirical evidence obtained was the E-SKP Job Performance Assessment could increase Organizational Commitment, both directly and if through intervening Job Satisfaction. This empirical evidence was supported by descriptive statistics at very high average values. In addition, the weak item was in the instructors who are worried if they stopped working now on the Organizational Commitment variable. furthermore, the instructors felt that they did not obtain an appreciation for their work performance on the Job Satisfaction variable, and the instructor did not feel that the supporting activities helped their teaching ability on the E-SKP Instructor Job Performance Assessment variable. This research had made various efforts to reduce or eliminate the occurrence of